Icons unearthed. Marvel [videorecording (Blu-Ray)] - Ferrigno, Lou; Gregg, Clark, 1962-; Straczynski, J. Michael, 1954- (Mill Creek Entertainment, 2024)
The Marvel Cinematic Universe is the most successful franchise of all time and it has changed the way movies are made. These films tell different characters' stories that all take place in one massive, interwoven universe. How did Marvel pull it off?